Amelioration of Compound 48/80-Mediated Itch and LL-37-Induced Inflammation by a Single-Stranded Oligonucleotide - Dondalska, Aleksandra; Rönnberg, Elin; Ma, Haisha; Pålsson, Sandra Axberg; Magnusdottir, Elin; Gao, Tianle; Adam, Lucille; Lerner, Ethan A.; Nilsson, Gunnar; Lagerström, Malin; Spetz, Anna-Lena (Frontiers in Immunology, 2020)
Numerous inflammatory skin disorders display a high prevalence of itch. The Mas-related G protein coupled receptor X2 (MRGPRX2) has been shown to modulate itch by inducing non-IgE-mediated mast cell degranulation and the release of endogenous inducers of pruritus. Various substances collectively known as basic secretagogues, which include inflammatory peptides and certain drugs, can trigger MRGPRX2 and thereby induce pseudo-allergic reactions characterized by histamine and protease release as well as inflammation. Here, we investigated the capacity of an immunomodulatory single-stranded oligonucleotide (ssON) to modulate IgE-independent mast cell degranulation and, more specifically, its ability to inhibit the basic secretagogues compound 48/80 (C48/80)-and LL-37 in vitro and in vivo. We examined the effect of ssON on MRGPRX2 activation in vitro by measuring degranulation in a human mast cell line (LAD2) and calcium influx in MRGPRX2-transfected HEK293 cells. To determine the effect of ssON on itch, we performed behavioral studies in established mouse models and collected skin biopsies for histological analysis. Additionally, with the use of a rosacea mouse model and RT-qPCR, we investigated the effect on ssON on LL-37-induced inflammation. We reveal that both mast cell degranulation and calcium influx in MRGPRX2 transfected HEK293 cells, induced by the antimicrobial peptide LL-37 and the basic secretagogue C48/80, are effectively inhibited by ssON in a dose-dependent manner. Further, ssON demonstrates a capability to inhibit LL-37 and C48/80 activation in vivo in two mouse models. We show that intradermal injection of ssON in mice is able to block itch induced via C48/80 in a dose-dependent manner. Histological staining revealed that ssON inhibits acute mast cell degranulation in murine skin treated with C48/80. Lastly, we show that ssON treatment ameliorates LL-37-induced inflammation in a rosacea mouse model. Since there is a need for new therapeutics targeting non-IgE-mediated activation of mast cells, ssON could be used as a prospective drug candidate to resolve itch and inflammation in certain dermatoses.